2019
DOI: 10.1111/bph.14771
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ATP release and CD73‐mediated adenosine formation sustain adenosine A2A receptor over‐activation in a rat model of Parkinson's disease

Abstract: Background and Purpose Parkinson's disease (PD) involves an initial loss of striatal dopamine terminals evolving into degeneration of dopamine neurons in substantia nigra (SN), which can be modelled by 6‐hydroxydopamine (6‐OHDA) administration. Adenosine A2A receptor blockade attenuates PD features in animal models, but the source of the adenosine causing A2A receptor over‐activation is unknown. As ATP is a stress signal, we have tested if extracellular catabolism of adenine nucleotides into adenosine (through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 71 publications
6
61
0
Order By: Relevance
“…This stems from the lack of evident peripheral changes in CD73-KO mice typified by the lack of altered blood pressure [22], cardiac output and ejection fraction [22], on running wheels during the light and dark phase of circadian rhythm [23], oxygen saturation erythrocytic and pH [23], blood glucose and 2,3-biphosphoglycerate levels [23]. This is in accordance with the presently observed lack of differences in the submaximal and maximum in a graded exercise test between CD73-KO mice and their WT littermates and the lack of alteration of spontaneous locomotion either in CD73-KO mice [12,15,24] or upon administration of the CD73 inhibitor α,β-methylene-ADP (AOPCP) [14]. Kulesskay et al [25] observed a hyperlocomotion in CD73-KO mice but attributed this difference to their isolation in cages with running wheels, contrasting with the collective housing in the present study.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This stems from the lack of evident peripheral changes in CD73-KO mice typified by the lack of altered blood pressure [22], cardiac output and ejection fraction [22], on running wheels during the light and dark phase of circadian rhythm [23], oxygen saturation erythrocytic and pH [23], blood glucose and 2,3-biphosphoglycerate levels [23]. This is in accordance with the presently observed lack of differences in the submaximal and maximum in a graded exercise test between CD73-KO mice and their WT littermates and the lack of alteration of spontaneous locomotion either in CD73-KO mice [12,15,24] or upon administration of the CD73 inhibitor α,β-methylene-ADP (AOPCP) [14]. Kulesskay et al [25] observed a hyperlocomotion in CD73-KO mice but attributed this difference to their isolation in cages with running wheels, contrasting with the collective housing in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, the ergogenicity of CD73-KO mice phenocopies the ergogenic profile of forebrain A 2A R-KO mice [8]. Indeed, CD73 and A 2A R are functionally coupled in different brain regions [1215], namely, in basal ganglia [12,14], A 2A R antagonism with SCH58261 is ergogenic [8], and the hyperlocomotion stimulated by SCH-58261 is reduced in CD73-KO mice [12].…”
Section: Discussionmentioning
confidence: 99%
“…The enzymes involved are CD39, which converts ATP to AMP, and CD73, which converts AMP to ADO. From the available evidence, this pathway, which protects against cell adhesion, is robust in endothelial cells [34,35]. As previously reported, in addition to Cx43 channels, both connexin37 (Cx37) channels and pannexin1 are potential pathways for ATP release.…”
Section: Discussionmentioning
confidence: 67%
“…A coordinated upregulation of 5′-NT and purinoceptor expression, particularly A2AR expression, has been suggested by previous reports such as in hippocampal astrocytes of human patients with mesial temporal lobe epilepsy (MTLE) [ 44 ], in a rat model of Parkinson's disease [ 45 ], and in a rat model of AD [ 46 ]. However, although our results regarding the A2AR receptor are in agreement with these previous reports, the decrease in 5′-NT activity was also indicated when neurospheres were treated with Al 3+ [ 13 ].…”
Section: Discussionmentioning
confidence: 92%